Coffee consumption habits with the addition of added ingredients correlated with obesity among females students in Semarang - Adinda Djasmin Setyo Putri; Ani Margawati Margawati; Rachma Purwanti; Ahmad Syauqy; Charysa Zaimatussoleha (AcTion: Aceh Nutrition Journal, 2023)
Chemical compounds found in coffee are good for health, but most Indonesians often consume coffee with added ingredients, such as sugar and milk. Thus, it will potentially increase the risk of obesity. This study aimed to analyze coffee consumption habits with added ingredients and their correlation with the incidence of obesity among female students in Semarang. The research design was cross-sectional, with 77 female students randomly selected.    This study was conducted from March to April 2021 in Semarang. All data collection process was conducted online. Data on coffee consumption habits, the kind of added ingredients, and the number of allowances were obtained through questionnaires. Furthermore, the food intake data were obtained from the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), physical activity data from the International Physical Activity Questionnaire Short Form (IPAQ-SF), and anthropometric data through self-anthropometric measurement guided by the researcher. Data were analyzed by the Chi-square test and multiple logistic regression test at a 95% CI. There was a relationship between coffee consumption habits and obesity according to the body mass index (p= 0,014), waist circumference (p= 0,001), and waist-hip ratio (p= 0,001). The multivariate analysis showed that the frequent consumption of coffee with added ingredients was correlated with the incidence of abdominal obesity based on waist circumference and waist-hip circumference ratio. It can be concluded that coffee consumption with added ingredients was correlated with the incidence of obesity.